Integrating Inquiry-Based Learning into Islamic Education Worksheets for Early Grade Learners: A Developmental Study - Nofiarti, Yessi; Zen, Zelhendri; Bentri, Alwen; Hakim, Ramalis (Pascasarjana Universitas KH. Abdul Chalim, 2026)
The current study seeks to explore Islamic religious education at the elementary level with the understanding that it has limitations presented through conventional teacher-centered teaching. Such limitations decrease student engagement and stifle creativity. The purpose of this research was to develop inquiry-based student worksheets with the objective of encouraging critical thinking and the importance of Islamic values in creating active participation in learning for Grade 1. This is a very relevant study, however, because early exposure to inquiry-oriented methods can significantly affect learning outcomes-cognitive and affective-for religious education. In employing the Research and Development (R&D) method through the ADDIE model, 13 Grade 1 students of SDN 05 Babukik participated in this study. The sources of data collection were questionnaires, observations, interviews, and pre- and post-tests, which were analyzed based on descriptive statistics and N-Gain tests. Expert validation was very feasible (content 95%, design 92%, media 87%), while practicality tests showed high acceptability by students and teachers. Effectiveness tests obtained moderate N-Gain score, indicating significant improvement in understanding. Thus, inquiry-based learning is indeed applicable within Islamic Religious Education and presents an innovative instructional model which encompasses the principles of inquiry into its materials. The study articulates the need for resources that are interactive and contextually relevant to promote meaningful understanding-student learning at primary level religious education.